Mesoscale and sub-mesoscale variability in phytoplankton community composition in the Sargasso Sea. (April 2016) - Cotti-Rausch, Bridget E.; Lomas, Michael W.; Lachenmyer, Eric M.; Goldman, Emily A.; Bell, Douglas W.; Goldberg, Stacey R.; Richardson, Tammi L.
Abstract: The Sargasso Sea is a dynamic physical environment in which strong seasonal variability combines with forcing by mesoscale (~100 km) eddies. These drivers determine nutrient, light, and temperature regimes and, ultimately, the composition and productivity of the phytoplankton community. On four cruises (2011 and 2012; one eddy per cruise), we investigated links between water column structure and phytoplankton community composition in the Sargasso at a range of time and space scales. On all cruises, cyanobacteria ( Prochlorococcus and Synechococcus ) dominated the phytoplankton numerically, while haptophytes were the dominant eukaryotes (up to 60% of total chl- a ). There were substantial effects of mesoscale and sub-mesoscale forcing on phytoplankton community composition in both spring and summer. Downwelling (in anticyclones) resulted in Prochlorococcus abundances that were 22−66% higher than at 'outside' stations. Upwelling (in cyclones) was associated with significantly higher abundances and POC biomass of nanoeukaryotes. In general, however, each eddy had its own unique characteristics. The center of anticyclone AC1 (spring 2011) had the lowest phytoplankton biomass (chl- a ) of any eddy we studied and had lower nitrate+nitrite (N+N <5 mmol m −2 ) and eukaryote chl- a biomass as compared to its edge and to the Bermuda Atlantic Time-Series station (BATS). At the center of cyclone C1 (summer 2011), we observed uplift of the 26.5 kg m −3 isopycnal and high nutrient inventories (N+N=74±46 mmol m −2 ). We also observed significantly higher haptophyte chl- a (non-coccolithophores) and lower cyanobacterial chl- a at the center and edge of C1 as compared to outside the eddy at BATS. Cyclone C2 (spring 2012) exhibited a deep mixed layer, yet had relatively low nutrient concentrations. We observed a shift in the taxonomic composition of haptophytes between a coccolithophore-dominated community in C2 (98% of total haptophyte chl- a ) and a non-coccolithophore community at BATS. In summer 2012, downwelling associated with anticyclone AC2 occurred at the edge of the eddy (not at the center), where AC2 interacted with a nearby cyclone. At the edge, we found significantly lower Synechococcus abundances and higher eukaryote chl- a compared to the center of AC2 and BATS. These along-transect nuances demonstrate the significance of small-scale perturbations that substantially alter phytoplankton community structure. Therefore, while seasonality in the North Atlantic is the primary driver of broad-scale trends in phytoplankton community composition, the effects of transient events must be considered when studying planktonic food webs and biogeochemical cycling in the Sargasso Sea. Highlights: Anticyclones (AC) had higher Prochlorococcus than Synechococcus cell abundances. Nanoplankton abundance and carbon biomass were highest in cyclones. AC1 center had lowest chl- a biomass of all eddies sampled. AC2 edge station had highest chl- a biomass where it interacted with nearby cyclone.